Three Essays on the Effects of Agricultural Land Expansion on Agricultural Sustainability in Sub-Saharan Africa - (:unkn) unknown (My University, 2023)
The aim of this thesis is to analyse the effects of agricultural land expansion on agricultural sustainability in sub-Saharan Africa. Though it is a prominent feature of these countries, its effects on agricultural sustainability have not been examined yet enough. Increasing agricultural land is hypothetically linked with social responsiveness like food security, economic aspect like structural change and environmental aspect such as biodiversity. This thesis shows in three essays that, agricultural land expansion can influence the prevalence of undernourishment, promote virtuous structural change and cause mammal species extinction. A panel analysis is conducted over 1990–2018 for 41 sub-Saharan African countries. The first essay uses the Generalised Method of Moments (GMM), the second essay employs a Pooled Multinomial Logit (POMLOGIT) model and the third, a pooled – Averaged Model. In all essays of the thesis, the three respective research hypotheses are rejected. The results disclose that agricultural land expansion influences three dimensions of agricultural sustainability in sub-Saharan Africa: Firstly, an increase of agricultural land by 1% reduces the prevalence of undernourishment by 0.23%, and helps to curb food insecurity. Secondly, it increases the probability of experiencing industrial-oriented structural transformation by 1.312, but by 1.089 services-oriented structural change. It promotes favourable transfer of agricultural labour towards the industrial sector. However, it causes serious damages to biodiversity. It is found that an expansion of agricultural land by 1% significantly increases the risk of extinction of endangered species, especially endemic mammals, by 0.0543. Therefore, the valuable benefits of agricultural land expansion must be weighed against the negative environmental impacts of converting forests and other natural habitat for agricultural purposes, increased carbon emissions, loss of ecosystem services and biodiv
Keywords: African Research